Escalating internationalization decisions: intendedly rational, but only limitedly so? - Björn Röber (Business Research, 2020)
The Uppsala model is commonly considered to be the pivotal approach in internationalization process research and often praised as particularly realistic. Yet at least implicitly and partially, it is also built on the assumption of rationally proceeding decision makers. This article challenges the behavioral assumptions of the Uppsala model and examines whether bounded rationality in the form of escalation of commitment has an influence on internationalization decisions. It demonstrates that this particular behavioral decision-making bias can be a critical factor. Thereby, this article indicates a major shortcoming of the Uppsala model, as it shows that internationalization processes can be maintained for non-rational reasons. It becomes clear that the bounded rationality of decision makers, particularly their limited cognitive capability, presents an issue that internationalization process research, including the Uppsala model, should give greater consideration to.
Keywords: 650; International business; Internationalization process theory; Bounded rationality; Empirical validity of the Uppsala model; Escalation of commitment